(untitled) (The Journal of Psychology and Sociology, 2016)
In the article the delegation of the VI International Congress of the Association of sociologists of Turkic World gives an overview about past event in Istanbul (Turkey, December 3-4, 2015), which focused on the history, society, and values of Turkic-speaking countries. The reports of the speakers were shown current problems of sociology, they discussed about sociologists cooperation in the framework for the exchange of experience of the Turkic space. As a result of the Congress of the Sociologists of Turkic World it revealed a special phenomenology and contribution to the Turkicspeaking countries in the modern ethnic, social and political diversity of the world. Sociologists reached to some important conclusions and organizational solutions, made a number of important results